Chiral Lithium Amides: Tuning Asymmetric Synthesis on the Basis of Structural Parameters. Issue 6 (20th December 2016) - Harrison‐Marchand, Anne; Barozzino‐Consiglio, Gabriella; Maddaluno, Jacques
Abstract: An overview on the structural arrangements adopted by Chiral Lithium Amides (CLAs), alone or in mixed complexes, is presented. These species are important reagents for asymmetric synthesis and understanding their organization is essential to improve their design and the reaction conditions. Abstract : An overview on the structural arrangements adopted by Chiral Lithium Amides (CLAs), alone or in mixed complexes, is presented. These species are important reagents for asymmetric synthesis and understanding their organization is essential to improve their design and the reaction conditions.